Review of Syaria Economy Disputes in Religious Courts within the Perspective of Small Claims Court (SCC) - Anita Afriana; Hazar Kusmayanti (Fiat Justisia: Jurnal Ilmu Hukum, 2021)
One of the absolute competencies of the Religious Court revolves around resolving sharia economy disputes. Quick, simple and inexpensive principles of the court must persist within Religious Court procedures, such as in sharia economy disputes relating to business disputes as regulated in Supreme Court Decree No. 14 of 2016 on Procedures in Sharia Economic Disputes. The solution in this way should be able to speed up commercial Shia dispute, but in fact, various obstacles were found. This article reviews the resolution of sharia economy disputes in Religious Court within the perspective of Small Claims Court implied through SC Decree No. 14 of 2016, along with the possible issues of Small Claims Court in Religious Court procedures. This research was conducted with a normative approach. Juridically SC Decree No. 14 of 2016 conforms with SC Decree No. 2 of 2015, now replaced with SC Decree No. 4 of 2019, permits parties to resolve certain nominal claims through a quicker dispute settlement procedure. Judges participate actively throughout the dispute resolution as Small Claims Court provides flexible interaction within formal courts. In practice, limitations such as the amount of sharia economy certified judges show that sharia economy cases are better resolved through standard procedure within the Civil Court. Other limitations, such as the insufficient electronic court (e-court) systems, limit dispute resolution capacity with further substantial limitations such as executorial clauses that are not yet regulated and can take more than 25 (twenty-five days).